Forestry Grey Literature in India and its Management - Deorani, S. C.; Dabral, S. L. (Indian Forester, 1997)
Informal forestry literature in India has been collected for over a century. The Indian Council of Forestry Research and Education (lCFRE) possesses around 2.61akhs of documents, classified into 3,600 files as per ODC System of classification. This paper highlights the importance of the documented forestry grey literature to research and its contribution in completing bibliographies of important forest tree species. It has also been planned to preserve these invaluable documents as per archival norms and capture them digitally on computer storage media viz. hard disks, CD-ROMs etc. for instant use of the forestry research workers and professionals.